Text Differences between Individual and Collaborative Writing: A Lexico Grammatical Perspective - Crawford, William J.; McDonough, Kim (rEFLections, 2017)
Although collaborative writing studies have found that collaboratively-written texts are more accurate than individually-written texts, previous studies in this framework have not identified differences in the grammatical features of texts written individually or collaboratively (Fernández-Dobao, 2012 Wigglesworth & Storch 2009; Storch & Wigglesworth, 2007; Storch, 2005). The current study further investigates variation in individual and collaborative texts by using a lexico-grammatical, corpus-driven approach (Chen & Baker, 2010; Hyland, 2008 a, b) to identify keyword differences and recurrent word sequences (lexical bundles). English L2 university students in Thailand (n = 99) wrote problem and solution paragraphs on the same topic in two different conditions: individually and collaboratively. The texts were analyzed to identify keyword differences and lexical bundles, and the lexical bundles were classified further as to their form and function. The results indicated differences between the two groups in their use of key words as well as the frequency of lexical bundles. Implications for these findings are discussed in light of the method used in previous collaborative writing studies as well as in the benefit of collaborative writing in general